The Dimension of the Teacher-Student Relationship: Frequent Language and its Conditioning Factors - Marta Blanco (Ignatianum University Press, 2021)
In our paper, we approach the question of the relationship between a teacher and a student from an interdisciplinary methodology that integrates philosophical, ethical, and pedagogical knowledge. Starting from a notion of a person as being open to reality and constitutively religated to it, we wish to discern how to establish adequate relationships with each of the individuals existing within it. Specifically, we focus on the interpersonal dimension that can be established in a school context. As a result of this reflection, we propose a series of guidelines in relation to some linguistic expressions, to be carried out according to the student's own understanding.